2016
DOI: 10.1515/tjj-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Engine Oil-cooling Problem during Idle Conditions on Pusher Type Turbo Prop Aircraft

Abstract: Aircraft engines need a cooling system to keep the engine oil well within the temperature limits for continuous operation. The aircraft selected for this study is a typical pusher type Light Transport Aircraft (LTA) having twin turbo prop engines mounted at the aft end of the fuselage. Due to the pusher propeller configuration, effective oil cooling is a critical issue, especially during lowspeed ground operations like engine idling and also in taxiing and initial climb. However, the possibility of utilizing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Upon validating the integrity of the numerical simulation (Premkumar et al , 2017), a five-bladed propeller with oil cooler installed in different radial locations in front of the propeller has been investigated further to ascertain the thrust loss. Numerous researches have been carried out in the area of propeller computation.…”
Section: Computational Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon validating the integrity of the numerical simulation (Premkumar et al , 2017), a five-bladed propeller with oil cooler installed in different radial locations in front of the propeller has been investigated further to ascertain the thrust loss. Numerous researches have been carried out in the area of propeller computation.…”
Section: Computational Studiesmentioning
confidence: 99%
“…Additionally, with a view to capturing the boundary layer effects, the maximum boundary layer thickness has been calculated, and 12 prism layers of the grid have been created within the calculated boundary layer thickness around the blade region (Zhang et al , 2015) as shown in Figure 4. After pre-processing, the rotational domain values are validated against empirical data (Premkumar et al , 2017).…”
Section: Computational Studiesmentioning
confidence: 99%
See 1 more Smart Citation